In search of lost time volume 1. The way by Swann's - Proust, Marcel, 1871-1922.; Prendergast, Christopher; Davis, Lydia (London ; New York : Penguin Books, 2003)
'In search of lost time' is Proust's masterpiece and was described by Somerset Maugham as the greatest novel of the 20th century.
v. 1. The way by Swann's / translated and with introduction and notes by Lydia Davis -- v. 2. In the shadow of young girls in flower -- v. 3. The Guermantes way -- v. 4. Sodom and Gomorrah -- v. 5. The prisoner and the fugitive -- v. 6. Finding time again.
Originally published: London : Allen Lane, 2002.
ENH
Translated from the French.
Keywords: France -- Social life and customs -- Fiction